Virtual Laboratory for Engineering Education: Review of Virtual Laboratory for Students Learning - Ibham Veza; Ahmed Sule; Nicky Rahmana Putra; Muhammad Idris; Ihwan Ghazali; Irianto Irianto; Ulka Chandini Pendit; Gipin Mosliano; Arasmatusy (The Indonesian Institute of Science and Technology Research, 2022)
E-learning is currently a rapidly growing trend which attempts to provide an infrastructural configuration that integrates and encompass learning content, services and tools as a single solution which can generate and deliver educational contents and training effectively, efficiently and cost-effectively. In advanced technical education, laboratories are essential learning spaces. Providing laboratory facilities at universities with limited funds and technical know-how is difficult due to the high expenses of installation and upkeep. In order to tackle these obstacles,